Hydrogeochemical Evolution of Interaction Between Surface Water and Groundwater Affected by Exploitation. Issue 3 (19th July 2018) - Guo, Xueru; Zuo, Rui; Wang, Jinsheng; Meng, Li; Teng, Yanguo; Shi, Rongtao; Gao, Xiang; Ding, Fei
Abstract: Hydrogeochemical evolution of interactions between surface water and groundwater is crucial for guaranteeing water supply quality in a riverside water source area. This study focuses on the seasonal and spatial characteristics of hydrogeochemical evolution affected by groundwater exploitation in the Hulan water source area using hydrochemical analyses and stable isotope tracers. Results show that the concentrations of major ions and total dissolved solids (TDS) increase considerably during the dry season. A bicarbonate water type is primarily produced by the dissolution of calcite, dolomite and gypsum, as well as the cation exchange and human activities. Along the typical infiltration path, the proportions of surface water increase with proximity to the river from 8%‐63% during the wet season to 11%‐84% during the dry season, which are attributed to an increased hydraulic gradient by exploitation. The typical path is classified into two zones. The first is the intensive mixing zone (within 1 km) with increasing concentrations of major ions and TDS due to mixing effect. The second is the exploitation influence zone (1‐3.3 km) with increased concentrations of Ca 2+, Mg 2+, SO4 2−, and HCO3 − during the dry season due to two reasons of seasonal variations in evaporation, stronger water‐rock interactions and mixing effects with increased surface water by exploitation. Abstract : Article impact statement : The hydrogeochemical evolution of surface water‐groundwater interaction is crucial for water supply quality in water source areas.